Comparative Analysis of Traditional and Modern Broiler Farms Using Google Colab t-test and Data Visualization - Galuh Adi Insani; Bayu Dwi Apri Nugroho; Ahmad Romadhoni Surya Putra; Andri Prima Nugroho (The University of Lampung, 2026)
This study aims to compare production performance between modern and traditional broiler farming systems in Indonesia and to evaluate the potential of digital data recording for decision-making support. Despite high feed prices, welfare concerns, and socioeconomic constraints, many farmers utilize modern technology to enhance their efficiency. Due to cost and production, many traditional farmers continue to use traditional farming practices. Production data were collected from modern and traditional farms in Gunungkidul District, Yogyakarta Province. Data were analyzed using Python-based t-tests and correlation heatmaps in the Google Colab environment. Data analysis revealed significant differences (p < 0.01) in feed intake (FI) and performance index (PI), but not in body weight (BW), average daily gain (ADG), or feed conversion ratio (FCR). Traditional and modern farming systems differ in FI and PI. Heatmaps enhance understanding of correlations, revealing a high association between FI, BW, and FCR (r ≥ 0.70), whereas modest relationships exist between FI, BW, and ADG. The results enable farmers to determine whether to enhance elements with moderate and strong correlations or solely those with strong correlations; they also permit the cooperative to assess farmers’ production based on broiler production and management practices.